Strategic Performance Measure, Innovativeness, Enterpreuneurship and Strategic Outcomes - Yuliansyah, Yuliansyah (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 2 (2018)DO - 10.24843/JIAB.2018.v13.i02.p12, 2018)
This study investigates the extent to which strategic performance measures (SPM) could enhance innovativeness and entrepreneurship by studying middle level of management in Indonesian financial institutions. The study analysed 157 data points using smartPLS. The study found that SPM leverages differentiation strategy only through innovativeness, rather than through entrepreneurship. This study also suggests that financial institutions in Indonesia should focus on innovativeness to differentiate themselves from their rivals, rather than trying to undercut rivals in price. Low-cost schemes cannot benefit those firms without innovativeness. Keywords: Entrepreneurship, innovativeness, strategic outcomes, strategic performance measures